Fatigue failure load and finite element analysis of multilayer ceramic restorations. Issue 1 (January 2019) - Archangelo, K.C.; Guilardi, L.F.; Campanelli, D.; Valandro, L.F.; Borges, A.L.S.
Highlights: Lithium disilicate monolayer group presented the highest mean of load-to-fracture. The lowest mean of fatigue failure load was obtained with bioinspired arrangements. The fracture originated from the bottom surface of the specimens. FEA models revealed the tensile stress region in the area of the fracture origin. Abstract: Objective: To evaluate the fatigue failure load via staircase approach and stress distribution via FEA of different ceramic configurations arranged in multilayers composed of ceramic materials with different elastic moduli and compare them to monolayer models. Methods: CAD–CAM ceramic blocks were used to shape 0.3 mm and 1.5 mm thick discs, corresponding to: feldspathic (F), 64 GPa; lithium disilicate (L), 95 GPa; and Yttrium-partially stabilized tetragonal zirconia (Y-TZP) (Y), 209.3 GPa. The 0.3 mm discs were arranged in 4 layers cemented with resin cement (Multilink N), and the 1.5 mm discs were not treated, in such a way that the final thickness of all specimens was 1.5 mm (±0.15 mm). The following 6 groups were tested: F (F: monolithic); L (L: monolithic); LLFF (L + L + F + F); FFLL (F + F + L + L); YLFF (Y + L + F + F); YLLF (Y + L + L + F). The loads-to-fracture were obtained using the biaxial flexural strength test until failure and the data were run using one-way ANOVA and Tukey's multiple comparisons ( α = 0.05) tests. The biaxial bending test was also simulated through finite element analysis (FEA) to identify the tensile stress generated at each layer of the groups. Mean fatigue failure load (100, 000 cycles; 20 Hz) was determined using the staircase approach. The fracture analysis was performed by stereomicroscope and scanning electron microscopy. Results: The load to fracture (N) were obtained as follows: L (592.9 ± 73.8) D > FFLL (319.78 ± 43.59) C > YLLF (246.75 ± 24.89) B > F (167.13 ± 9.84) A > YLFF (166.51 ± 15.24) A > LLFF (165.46 ± 22.75) A ; and the fatigue failure load (N): L (310.92 ± 26.73) F > FFLL (190.17 ± 8.32) E > F (106.21 ± 2.81) D > YLLF (96.48 ± 5.73) C > YLFF (89.56 ± 2.38) B > LLFF (77.23 ± 6.33) A . The origin of all of the tested specimens was located at the tensile region of the discs, as encountered in FEA. Significance: The material under tensile stress is determinant for the restoration's strength and the adhesive interface negatively influenced the mechanical behavior of the multilayer structures.